Seapower a guide for the twenty-first century - Till, Geoffrey (Cass series: naval policy and history ;, 2018)
This book investigates the consequences of all this for the developing nature, composition and functions of all the world's significant navies, and provides a guide for anyone interested in the changing and crucial role of seapower in the 21st century. Seapower is essential reading for all students of naval power, maritime security and naval history, and highly recommended for students of strategic studies, international security and International Relations.